Cost-Benefit Analysis of Government Policies in Supporting SMEs in COVID-19 Pandemic - Nelly Romauli Simamora; Ratna Dwi Lestari; Dicky Andriyanto; Izzato Millati (UPT Penerbitan Universitas Jember, 2021)
The SMEs sector is often dubbed the hero of saving the nation's economy. This is motivated by the economic crisis that occurred in 1998 where as many as 64 percent of SMEs did not experience any impact and did not experience changes in turnover. One of the priorities that must be saved in restoring the economy due to the Covid 19 Pandemic. This study aims to evaluate the policies that have been implemented by the Government in an effort to save SMEs from the impact of the COVID-19 Pandemic through a cost-benefit analysis tool using the BCR (Benefit Cost Ratio) method. The research method we use is a qualitative descriptive method, namely the researcher collects and describes the phenomena that occur as a result of the COVID-19 pandemic and the impact it has on the economic sector, especially SMEs in Indonesia. Researchers also made use of secondary data from various literatures such as books, articles, and homepages to access the latest data and information related to policies to save SMEs from the impact of the COVID-19 pandemic. The results showed that the government policy in supporting the SMEs sector was feasible to implement. This is because the benefits are greater than the costs indicated by the BCR results of 3.2 or greater than 1. Keywords: SMEs, Cost-Benefit Analysis, Government Policy